Space zoning concept-based scheduling model for repetitive construction process - Cho, Kyuman; Hong, Taehoon; Hyun, Chang Taek (Journal of Civil Engineering and Management, 2013)
Many researchers have studied effective space zoning to reduce the duration of a construction project and interference among work tasks. These studies, however, attempted to plan the construction schedule using the space zoning concept based on network-based scheduling methods. Accordingly, it was difficult to reflect the representative characteristics of space zoning, such as iteration and overlapping. To overcome such limitations of existing methodologies and to achieve schedule reduction of a construction project by maximizing productivity, a Space zoning Concept-based scHEduling ModEl (SCHEME) for repetitive construction processes that adopt simulation techniques was developed in this study. The result of the application of the developed model to actual construction cases shows that the model reflects well the space-zoning characteristics, and in terms of the reduction of the construction duration, the model yielded a superior outcome in nonspace-zoning cases. The model developed in this study is expected to produce an excellent effect on the repetitive construction processes, in terms of construction duration.